Crafting Sustainable Development Solutions: Frugal Innovations of Grassroots Entrepreneurs - Pansera, Mario (2016)
A shift in the entrepreneurial landscape is taking place brought about by grassroots innovators with little formal education and technological knowhow, living and working in penurious environments. This research represents an emerging third wave of literature on Bottom of the Pyramid innovation, where products are offered for and by the underserved. Using primary and secondary data derived from four cases of grassroots entrepreneurs in the Indian Subcontinent, the study explores the phenomenon where resource scarce entrepreneurs craft solutions that are environmental friendly, with low overall ownership costs, and use locally available material. We argue that the grassroots phenomenon can be fruitfully exploited to achieve the new Sustainable Development Goals proposed by the UN as a post-2015 strategy for the future of global governance. These innovations might have a tremendous impact not only in terms of serving unmet and ignored consumer needs, but also longer term impacts through enhanced productivity, sustainability, poverty reduction and inclusion promotion.